The Effect of Project-Based Learning Model on Problem Solving Skills in Coastal PAUD Institutions - Niyarci; Yuli Kurniawati Sugiyo Pranoto; Sunawan (JURNAL PENDIDIKAN USIA DINI, 2025)
Children's involvement in learning can provide concrete learning experiences for the child's growth and development process. The purpose of this study was to determine the effect of project-based learning model on problem solving skills in PAUD institutions in coastal areas. This study used a quantitative experimental method with the Non-equivalent Pretest - Post Test Control Group Design model. The research subjects consisted of 25 children in classes B1 and B2 of Islamic Kindergarten 01 Kauman Juwana. Data collection techniques using observation, questionnaires and documentation. Data analysis techniques using paired sample t-test.  The results of data analysis show that there is an effect of project-based learning models on children's problem solving in coastal PAUD institutions aged 5-6 years. This is indicated by the acquisition of a sig value that is smaller than the predetermined significance level of 0.000 < 0.05. The results of this study show that although conventional learning methods have an effect, the effectiveness of project-based learning in improving problem solving is much higher. This suggests that a more active and engaged approach, such as project-based learning, can encourage children to think critically and creatively, which is essential in the development of problem solving skills. Project-based learning is important to consider in the development of future curriculum and learning methods, so that children can gain a more optimal learning experience